2006
DOI: 10.1002/hlca.200690236
|View full text |Cite
|
Sign up to set email alerts
|

Analogues ofα-Campholenal (= (1R)-2,2,3-Trimethylcyclopent-3-ene-1-acetaldehyde) as Building Blocks for (+)-β-Necrodol (= (1S,3S)-2,2,3-Trimethyl-4-methylenecyclopentanemethanol) and Sandalwood-like Alcohols

Abstract: To complete our panorama in structure-activity relationships (SARs) of sandalwood-like alcohols derived from analogues of a-campholenal (= (1R)-2,2,3-trimethylcyclopent-3-ene-1-acetaldehyde), we isomerized the epoxy-isopropyl-apopinene (À)-2d to the corresponding unreported a-campholenal analogue (+)-4d (Scheme 1). Derived from the known 3-demethyl-a-campholenal (+)-4a, we prepared the saturated analogue (+)-5a by hydrogenation, while the heterocyclic aldehyde (+)-5b was obtained via a Bayer-Villiger reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Pamingle et al reported an efficient method of isomerizing the exocyclic double bond of β-necrodol to the endocyclic double bond of R-necrodol (8), but their synthesis of β-necrodol was inefficient (9). However, β-necrodol has been synthesized by several other routes (10)(11)(12)(13)(14)(15), with that reported by Monti et al being both short and proceeding with complete 1,3-diastereoselection (14). Here, we describe a convenient synthesis of the racemic grape mealybug sex pheromone by combination and further optimization of elements from several of these syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…Pamingle et al reported an efficient method of isomerizing the exocyclic double bond of β-necrodol to the endocyclic double bond of R-necrodol (8), but their synthesis of β-necrodol was inefficient (9). However, β-necrodol has been synthesized by several other routes (10)(11)(12)(13)(14)(15), with that reported by Monti et al being both short and proceeding with complete 1,3-diastereoselection (14). Here, we describe a convenient synthesis of the racemic grape mealybug sex pheromone by combination and further optimization of elements from several of these syntheses.…”
Section: Introductionmentioning
confidence: 99%